Parry - Essien, Stephen Akpan (Evans Brothers (Nigeria Publishers) Ltd, 1988)
This is a story that strongly demonstrates a religious belief in destiny. It portrays a society where old values are gradually giving way to new ones; where a man's success is no longer measured only in terms of the largeness of his farm and the number of wives he has; but also in terms of how much of the white man's wisdom he has acquired. On the other hand, it presents a society where women are afforded the opportunity of acquiring the white man's knowledge just like their mal counterpart.
Keywords: Juvenile Fiction / Adventure